2007
DOI: 10.1002/jor.20363
|View full text |Cite
|
Sign up to set email alerts
|

Towards development of a nonhuman primate model of carpal tunnel syndrome: Performance of a voluntary, repetitive pinching task induces median mononeuropathy in Macaca fascicularis

Abstract: This study investigated changes in median sensory nerve conduction velocity (SNCV) over several weeks of exposure to a voluntary, moderately forceful, repetitive pinching task performed for food rewards by a small sample of young adult female monkeys (Macaca fascicularis). SNCV, derived from peak latency, decreased significantly in the working hands of three of the four subjects. The overall decline in NCV was 25%-31% from baseline. There was no decrease in SNCV in the contralateral, nonworking hands. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…10 In contrast to our human study, we did not find increased serum IL-6 in this study, a result consistent with findings of a repetitive pinching task in a nonhuman primate model 6 and a study examining patients with carpal tunnel syndrome. 19 However, there was no detectable serum TNFa in those two studies 6,19 results differing from ours. Species differences in cytokine response profiles, the detection system used, and inherent differences in the injury induced may account for these varying results.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…10 In contrast to our human study, we did not find increased serum IL-6 in this study, a result consistent with findings of a repetitive pinching task in a nonhuman primate model 6 and a study examining patients with carpal tunnel syndrome. 19 However, there was no detectable serum TNFa in those two studies 6,19 results differing from ours. Species differences in cytokine response profiles, the detection system used, and inherent differences in the injury induced may account for these varying results.…”
Section: Discussionsupporting
confidence: 85%
“…For example, here, the rats flex their wrists as well as extend their elbow and shoulder, increasing the involvement of more regions than in the pinch task. 6 Prolonged, intensive cycling results in short-lived increases (immediate to 2 h postexercise) of several serum cytokines, 13,14 presumably after release from contracting muscles. 21 However, it is unlikely that muscle contractions contributed to our increased serum cytokines and chemokines because we collected serum at 18-36 h after completion of the final task session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support this viewpoint, Reference [20] reported that more than 35 percent of the students using Tablet PC at home would not utilize a desk or table. And over 50 percent of the students experienced discomfort in eyes, neck, head, wrist and back.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Those suggested maximum limits are indicated in Table 1. 4. An operant rat model of WMSD Several animal models have been developed to study WMSDs and have shown that repetitive hand activities induce sensorimotor dysfunction [27][28][29][30][31][32][33]. A model developed in our laboratory is a unique operant rat model of voluntary reaching and grasping (Figure 1; [7,34]).…”
Section: Ibuprofenmentioning
confidence: 99%